Analisis Materi Pembelajaran IPS SD Kelas VI Tema 1-3 dalam Buku Penerbit Kemendikbud di Sekolah Dasar - Muhammad Syahrul Irawan; Wawan Priyanto; Singgih Adhi Prasetyo (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The focus of research is how to analyze social studies learning material in primary school class VI themes 1-3 in the Kemendikbud publishers book. The purpose of this research is to find out and analyze how the social studies learning material for primary school class VI themes 1-3 in the book publish by Ministry of Education and Culture. This type of research is qualitative research. The research was conducted at SDN Tambahsari and SDN Payang 3 Pati for the 2020/ 2021 school year. Sources of data in this study were thematic textbooks class VI themes 1-3 published by the Ministry of Education and Culture, class VI teachers, and lecturers. The result of this study indicate that the scope of Social Sciences (IPS) class VI themes 1-3 in a book published by Ministry of Education and Culture contains geography, history, and economic learning material. In each theme there are only ono and two scopes of Social Sciences (IPS). Geographical scope is in theme 1, historical scope is in theme 2 and theme 3, economic scope is in theme 1 and theme 3.